STUDI DESKRIPTIF PERILAKU KOMPLAIN DAN MOTIF KOMPLAIN PELANGGAN RESTORAN DI HOTEL X SURABAYA - Chandra Ruslan (Perpustakaan Universitas Surabaya, 2013)
Hotel X is one of star hotel at Surabaya, and almost of the guest is domestic tourist. According to tghe interview with the secretary of manager showing that there is many of complaint about the service of”X” Resto at “X” Hotel in Surabaya. The result of pre test showing that there is 23 respondents who state that visited ”X” Resto at “X” Hotel in Surabaya. During June – September 2012., and there is 8 of respondents who state felt unconfortable of the service but no complaint, and there are 10 of respondents who state compalint. The purpose of this research is explaining the complint behavior at ”X” Resto at “X” Hotel in Surabaya. The research design is decriptive which explore the customer complaint behavior at ”X” Resto in “X” Hotel in Surabaya according the demographic data: age, education level, household level, and gender. The number of samples are 102 samples. Data analysis method by statistic descriptive, crosstabulation, and chi square analysis. This research showing that according to the whole of complaint behavior, the top and the most aggree by consumer is warning to the family and frends. The lower of complaint behavior is complaint to the consumers protection agency and the highest complaint motive is take problem solving. There is association among the complaint bahevior and age, education level, and gender